Analysis of the Impacts of Exchange Rate Variations on the Benin Economy: The Case of the FCFA and the Naira - Adom, Marius Idossou; HOUNSOU, RÉMY; Camara, Alhassane (My University, 2017)
Benin shares with Nigeria, about 773 kilometers of land border. The two countries are linked by very long socio- cultural and historical relationships. Beyond these affinities, their geographical proximity allows them to trade based on their economic disparities. Consequently, Nigeria's economic shocks have repercussions on Benin, in this case those of its currency. In particular, the decision of the Central Bank of Nigeria in June 2016 to let the exchange rate of the currency fluctuate freely has seriously affected the Beninese economy. This study assesses the impacts of a variation in the exchange rate between the CFA and the Naira on Benin using a computable general equilibrium (CGE) model. Thus, we were able to prospect the probable impacts of a common currency (ie a unit exchange rate) for Benin and Nigeria. Our results showed that the known decline in naira prices in June 2016 compared to 2010 had a negative and severe effect on government revenues, which declined by 19.6% for export taxes and 14.4% for internal market taxes (including imports). Similarly, the decline resulted in a sharp decline in inflation of 14% and nominal GDP of 12.4%, while real GDP rose by 2.2%. Consumption fell by 12.3% at 13.8% for rural households as against 10.9% for urban households. Thus, the depreciation of the Naira is proving to be a source of deepening inequality in Benin. This decline in Naira prices also affects employment and drives the economy towards trade and services to the detriment of productive sectors such as agriculture and industry. It penalizes unskilled workers while skilled workers take refuge in the administration. We conclude that overall, Benin is favored by a strong Naira rather than a weak Naira. In particular, a common currency scenario is not favorable for Benin.
Keywords: Naira; CFA franc; exchange rate; imports; exports; CGE